Microsurgical re-treatment of an endodontically treated tooth with an apically located incomplete vertical root fracture: a clinical case report - Silvio Taschieri; Massimo Del Fabbro; Ahmed El Kabbaney; Igor Tsesis; Eyal Rosen; Stefano Corbella (Korean Academy of Conservative Dentistry, 2016)
Although it is challenging, the early diagnosis of a vertical root fracture (VRF) is crucial in order to ensure tooth preservation. The purpose of this clinical case report was to describe reparative surgery performed to treat a tooth affected by an incomplete VRF. A 26 year old male patient was suspected to have a VRF in a maxillary left central incisor, and an exploratory flap was performed in order to confirm the diagnosis. After detecting the fracture, the lesion was surgically treated, the fracture and the infected root-end were removed, and a platelet-rich plasma membrane was used to cover the defect in order to prevent bacterial migration. A 24 month clinical and radiological follow-up examination showed that the tooth was asymptomatic and that the healing process was in progress. The surgical approach described here may be considered an effective treatment for a combined endodontic-periodontal lesion originating from an incomplete VRF and a recurrent periapical lesion.